Design of an architectural framework for a health assessment information system for urban agriculture interventions in low-resource settings using a soft systems approach to information system design - Idzerda, Leanne (Stellenbosch : Stellenbosch University, 2019)
Thesis (PhD)--Stellenbosch University, 2019.